2018
DOI: 10.1001/jamadermatol.2018.3281
|View full text |Cite
|
Sign up to set email alerts
|

Prescribed Exercise With Compression vs Compression Alone in Treating Patients With Venous Leg Ulcers

Abstract: IMPORTANCEExercise is recommended as an adjuvant treatment for venous leg ulceration (VLU) to improve calf muscle pump function. However, the association of exercise with VLU healing has not been properly aggregated, and the effectiveness of different exercise interventions has not been characterized. OBJECTIVETo summarize the association of different exercise interventions with VLU healing when used as an adjuvant to any form of compression.DATA SOURCES The Cochrane Controlled Trials Register, MEDLINE, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 40 publications
1
57
0
5
Order By: Relevance
“…Three SRs related to weight management were published, including one on nutritional status and supplements and two on exercising . The authors reported that increased body mass index was associated with delayed wound healing, but the evidence of effectiveness of weight management in improving VLU healing is lacking .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three SRs related to weight management were published, including one on nutritional status and supplements and two on exercising . The authors reported that increased body mass index was associated with delayed wound healing, but the evidence of effectiveness of weight management in improving VLU healing is lacking .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier SR of the studies reporting the effect of exercise on VLU healing in patients indicates that the findings reporting positive effects were insignificant and further studies are necessary . Latest SR of studies on prescribed exercising indicates that there is low quality evidence of its effect on VLU healing, which is sufficient to recommend this adjuvant therapy for VLU patients…”
Section: Resultsmentioning
confidence: 99%
“…Physical exercises aimed at activating the muscle pump 23 such as toe raises have been used with some success for healing venous leg ulcers, 24 and it has been shown that even minor movements of the foot are effective 25 . Furthermore, it has been found that poor muscle pump function can be improved by regular activation 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Progresif güçlendirme egzersizleri yapılması baldır kas pompası fonksiyonunu iyileştirmektedir. Alt ekstremite egzersizi aktif planter fleksiyona direnç (4 kg) en az 7 gün, her gün en az üç set şeklinde ve altı dakika süreyle 12 hafta boyu yapılması tavsiye edilmektedir (18). Beslenme ve Hidrasyon Protein ve aminoasitler, enerji, vitaminler (A, E) ve çinko yara iyileşmesi için gereklidir.…”
Section: Venöz Ayak üLserinde Tedavi Yöntemlerunclassified